Management of late hemorrhagic radiation cystitis in patients of carcinoma cervix with special reference to 1% alum irrigation and its safety: a clinical study in a tertiary care centre - Barua, Sasanka Kumar; Das, Nabajeet; Baruah, S. J.; P., Rajeev T.; Bagchi, Puskal Kumar; Sarma, Debanga; Phukan, Mandeep (International Journal of Advances in Medicine, 2019)
Background: Radiation cystitis is a well-known complication arising from radiation therapy in pelvic malignancies. Haematuria is usually the main presenting symptom of radiation cystitis, which can range from mild to severe refractory and life-threatening forms. There are various forms of treatment ranging from intravesical instillations like alum, formalin, prostaglandins and pentosan sulphate; hyperbaric oxygen therapy to surgical treatment like cystoscopic fulguration, arterial ligation and cystectomy. Here authors aimed to find the efficacy of 1% alum irrigation in controlling haematuria due to radiation cystitis and to correlate its use with change in clinical status and biochemical parameters. Methods: This retrospective study was done for a period from July 2010 to July 2017 which included all female cervical cancer patients with intractable haematuria due to radiation cystitis. Only patients with normal renal function were included. Irrigation with 0.9% NS, hem coagulase and subsequently 1% alum irrigation were given. Failed cases underwent cystoscopic fulguration. Results: Average age of presentation was 59.79 years. Of the 34 patients 20 (64.51%) patients showed complete response, 4 (12.9%) patients showed partial response and 7 (22.58%) patients had no response to alum irrigation and cystoscopic fulguration were done in these cases. There was no significant change in vital parameters and biochemical parameters except increased prothrombin time (<0.001). Conclusions: No standard of care therapy is presently available for patients with hematuria following radiation cystitis although there is big armamentarium of therapies. Authors found that 1% alum irrigation is safe and efficacious for these patients although normal renal function is a prerequisite.